P2 Interventions to improve safety of parenteral nutrition use on a paediatric intensive care unit. Issue 2 (19th January 2018) - Harrington, Aoife; Makhecha, Sukeshi; Bentley, Sian; Kollman, Anja; Osborne, Sarah; Zizkova, Eva
Abstract : Aim: Parenteral nutrition is a high risk treatment, and under- or over-infusion can have serious consequences for patients. Following several errors where parenteral nutrition (PN) was administered at incorrect rates, including incidents of vamin and lipid rates being switched, we aimed to reduce errors causing harm related to PN prescribing and administration. Method: The local incident reporting system was used to identify errors and trends involving PN. The most common errors involved incorrect rates being either prescribed or administered. A series of interventions were developed between March 2014 and December 2015 aimed at reducing errors. Unit staff were surveyed and PN bag changeover was moved from day to night shifts. The nursing PN administration guideline was updated and relaunched to reinforce the correct procedure. Usual practice on the unit is for nurses to titrate PN to maximum rates according to fluid allowance. Prescription rates were audited, multidisciplinary team (MDT) staff surveyed and daily prescribing of administration rate ranges was implemented with MDT support. PN education sessions were targeted at all staff via a short 'bootcamp' format repeated over three weeks and a session at weekly medical teaching. The sessions covered general information, risks and examples of both common and serious errors. Results: Planned changes were accepted and supported by the unit staff. The initial prescription audit found 100% of patients had inaccurate rates prescribed and 43% of patients had rates running above those prescribed. Re-audit of prescriptions following the change showed that the correct rate ranges were being updated daily and PN was administered at or below maximum rates. Through the bootcamp sessions we identified some areas of confusion and variations in practice; the administration guideline was further updated as a result. Error monitoring showed an initial increase in reported errors for 2015. These were mainly near miss reports (no harm) but also included two incidents where lipid and vamin rates were switched. This was followed by a reduction in errors in 2016 with no further incidence of lipid and vamin rates switched. Conclusion: The interventions implemented did reduce the incidence of PN errors causing harm. We believe the decrease in errors was due to the cumulative effect of changes and increased awareness. The initial increase in reported errors in 2015 may have been due to increased awareness and reporting. We considered the possibility of interventions increasing errors but discussion with staff involved suggested this was not a factor. MDT involvement is crucial, as is good communication with all staff throughout the change process. We will continue to encourage near miss reporting and monitor on an ongoing basis to ensure the change is sustained, and target new staff to maintain these improvements.